Parp1 hyperactivity couples DNA breaks to aberrant neuronal calcium signalling and lethal seizures. (1st May 2021) - Komulainen, Emilia; Badman, Jack; Rey, Stephanie; Rulten, Stuart; Ju, Limei; Fennell, Kate; Kalasova, Ilona; Ilievova, Kristyna; McKinnon, Peter J; Hanzlikova, Hana; Staras, Kevin; Caldecott, Keith W
Abstract: Defects in DNA single‐strand break repair (SSBR) are linked with neurological dysfunction but the underlying mechanisms remain poorly understood. Here, we show that hyperactivity of the DNA strand break sensor protein Parp1 in mice in which the central SSBR protein Xrcc1 is conditionally deleted ( Xrcc1 Nes‐Cre ) results in lethal seizures and shortened lifespan. Using electrophysiological recording and synaptic imaging approaches, we demonstrate that aberrant Parp1 activation triggers seizure‐like activity in Xrcc1‐defective hippocampus ex vivo and deregulated presynaptic calcium signalling in isolated hippocampal neurons in vitro . Moreover, we show that these defects are prevented by Parp1 inhibition or deletion and, in the case of Parp1 deletion, that the lifespan of Xrcc1 Nes‐Cre mice is greatly extended. This is the first demonstration that lethal seizures can be triggered by aberrant Parp1 activity at unrepaired SSBs, highlighting PARP inhibition as a possible therapeutic approach in hereditary neurological disease. SYNOPSIS: Excessive PARP1 activity at unrepaired DNA single‐strand breaks in Xrcc1‐defective brain causes aberrant synaptic calcium signaling, seizures, and shortened lifespan. These effects are prevented by Parp1 inhibition, revealing possibilities for the treatment of human neurological disease. Parp1 hyperactivity triggers aberrant synaptic activity in Xrcc1‐mutated neurons Parp1 hyperactivity causes seizures and shortened life‐span Aberrant synaptic and seizure‐like activity are prevented by Parp1 inhibition or deletion Abstract : Excessive PARP1 activity at unrepaired DNA single‐strand breaks in Xrcc1‐defective brain causes aberrant synaptic calcium signaling, seizures, and shortened lifespan. These effects are prevented by Parp1 inhibition, revealing possibilities for the treatment of human neurological disease.